Análise das propriedades de medida da Escala Tampa de Cinesiofobia-11 em pacientes com fibromialgia - Salvador, Evany Maira Espirito Santo (2019)
The purpose of this masters dissertation was to analyze the measurement properties of the brazilian-portuguese version of the Tampa Scale of Kinesiophobia-11 in patients with fibromyalgia. Three assessments were carried out: baseline assessment (n=130), 15 days after baseline (n=54) and eight weeks after baseline (n=51). The data collected at baseline were used to evaluate internal consistency, criterion validity and construct validity and ceiling and floor effects, at 15 days after baseline to evaluate reliability and measurement error, and at eight weeks after baseline to evaluate responsiveness. The Tampa Scale of Kinesiophobia-11 showed adequate internal consistency (Cronbach's alpha=0.77 (alpha if item deleted: 0.74 to 0.77)), substantial reliability (intraclass correlation coefficient2,1=0.85 (95% confidence interval: 0.75 to 0.90)), good measurement error (standard error of measurement: 2.65 points (7.81%)) and smallest detectable change of 6.16 points. In relation to the validity, Tampa Scale of Kinesiophobia-11 showed a positive and good correlation with the original Tampa Scale of Kinesiophobia (r=0.84, p<0.01), a positive and moderate correlation with the Pain Catastrophizing Scale (r=0.55, p<0.01), positive and weak correlation with the Pain Numerical Rating Scale (r=0.25, p<0.01), positive and moderate correlation with the Beck Depression Inventory (r=0.39, p<0.01) and no correlation with the Patient Specific Functional Scale (r=0.11, p=0.23). Finally, the Tampa Scale of Kinesiophobia-11 showed a low responsiveness in patients with fibromyalgia with less than 40% of the hypotheses confirmed. The Tampa Scale of Kinesiophobia-11 is consistent, reliable and appropriate to assess patients with fibromyalgia in the clinical context. However, the scale is not indicated to assess the effects of the treatment in these patients.